1999
DOI: 10.2307/3579828
|View full text |Cite
|
Sign up to set email alerts
|

Protein-DNA Complexes Containing DNA-Dependent Protein Kinase in Crude Extracts from Human and Rodent Cells

Abstract: The DNA-dependent protein kinase (DNA-PK) is composed of a large catalytic subunit (DNA-PKcs) and a DNA-binding protein, Ku. Cells lacking DNA-PK activity are radiosensitive and are defective in DNA double-strand break repair and V(D)J recombination. Although much information regarding the interactions of Ku with DNA ends is available, relatively little is known about the interaction of DNA-PKcs with DNA-bound Ku. Here we show, using electrophoretic mobility shift assays, that chemical crosslinkers enhance the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…When DNA DSBs occurred, Ku70 and Ku80 bind rapidly with the DNA ends, promoting the inward sliding of Ku70 and Ku80 along the length of DNA, at the same time recruiting PRKDC to assemble a DNA-PK heterotrimer (39). Formation of this complex may also be promoted through interactions with heterodimeric ILF2 and ILF3 (40). Our proteomic data showed that all of these proteins (Ku70, Ku80, PRKDC, ILF2 and ILF3) were up-regulated under hypoxic conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When DNA DSBs occurred, Ku70 and Ku80 bind rapidly with the DNA ends, promoting the inward sliding of Ku70 and Ku80 along the length of DNA, at the same time recruiting PRKDC to assemble a DNA-PK heterotrimer (39). Formation of this complex may also be promoted through interactions with heterodimeric ILF2 and ILF3 (40). Our proteomic data showed that all of these proteins (Ku70, Ku80, PRKDC, ILF2 and ILF3) were up-regulated under hypoxic conditions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our data suggest that although serine 51 can be phosphorylated by DNA-PK in the context of the recombinant Ku70 protein, under the conditions used in our study, where the Ku70/80 heterodimer is present in excess of DNA-PKcs, this residue is not the major site of phosphorylation. With this in mind, it is interesting to note that Ku is present in large molar excess over DNA-PKcs in both human cells (46) and rodent cells (47), suggesting that in the cell phosphorylation of Ku heterodimer may occur predominantly under conditions in which the majority of the Ku is not present in a complex with DNA-PKcs. During our studies we did not detect a phosphopeptide containing phosphorylated serine 51 either by either tricine gel electrophoresis or by HPLC followed by protein sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…While the disparity in wortmannin sensitivity could be due to technical factors such as the differences in preparation of the various extracts, it could reflect the levels of DNA-PKcs. DNA-PK activity is typically 50 -100-fold lower in hamster and other rodent cell extracts than in human cell or Xenopus egg extracts (49 -52), and electrophoresis mobility shift assays as well as Western blot assays are consistent with this difference being due to a much lower level of DNA-PKcs protein in rodent cells (53), including CHO cells. 2 Thus, a hypothesis consistent with all of the available data is that although DNA-PKcs is not required for accurate end joining in vitro, sufficient quantities of it produce an inhibitory effect that can be alleviated by activation of its kinase activity.…”
Section: Fidelity Of Dna End Joiningmentioning
confidence: 98%